Pain Perception in Cataract Surgery: Topical versus Peribulbar Anaesthesia - Maharjan, Indraman; Shrestha, Eliya; Gurung, Babita; Gurung, Hara Maya; Adhikari, Hari Bikram; Baral, Pawan (Nepalese Journal of Ophthalmology, 2021)
Introduction: The requirement for very deep akinesia has decreased with the use of modern phacoemulsification technique for cataract surgery. The use of topical anesthesia has increased as a way to reduce complications associated with anaesthesia with injection and to allow the most rapid visual recovery. The objective of this study was to assess the patient reported pain in phacoemulsification cataract surgery under topical anaesthesia versus peribulbar anaesthesia administered using an injection. Materials and methods: The subjects for this study were the patients undergoing phacoemulsification cataract surgery at HEH. Subjects were divided into two groups, one having topical anaesthesia for phacoemulsification and the other having peribulbar anaesthesia with injection. The data for the study was collected in a ten point visual analogue graphic pain scale. After the surgery was over the patients reported on the felt pain wherein the scale zero was assigned for no pain at all, 1 to 3 for mild pain, 4-6 for moderate pain and 7-10 for severe pain. Results: In total, 366 subjects received peribulbar anaesthesia and 336 subjects received topical anaesthetic drops. The mean pain score between the two groups was found to be higher in the peribulbar injection group (p <0.001). The mean pain score for both males and females was found to be higher in the peribulbar injection group (p<0.001 for both genders). Conclusion: Topical anaesthesia for phacoemulsification cataract surgery tends to cause less pain and discomfort for patients.